A new Clathria (Demospongiae, Microcionidae) from Peru occurring on rocky substrates as well as epibiontic on Eucidaris thouarsii sea urchins - Aguirre, L. Karem; Hooker, Yuri; Willenz, Philippe; Hajdu, Eduardo (Zootaxa, 2011)
Southeastern Pacific sponges (Phylum Porifera) range among the world’s least known faunas, with only 13 species reported to date from the entire Peruvian coast. This state of affairs motivated the onset of two large, cooperative, exploratory initiatives, with the aim of mapping sponge richness and distribution in the area: Proyectos ESPER and EsponjAS. Over 800 specimens have been collected in Peru since 2007, with identifications still in progress. Among these, a sponge species originally thought to be an exclusive epibiont on Eucidaris thouarsii sea urchins, relatively conspicuous on Peru’s Punta Sal region. This sponge, latter found to occur on additional substrates too, is described as a new species of Clathria (Microciona). Cidarid density ranged between 1.5 and 12/m 2 , and largest diameter of the tests between 3.2 and 5.6 cm. Total number of spines on each sea urchin varied between 68 and 96, and percent sponge coverage of these, between 18.2 and 75.7. There appears to be only a slight tendency for increased sponge coverage on larger sea urchins, so there may be factors, other than sea urchin age, shaping this association. Clathria (Microciona) aculeofila sp. nov. can be markedly dominant as an epibiont on E. thouarsii, albeit the great sponge richness in the area. This is in contrast to the allegedly opportunistic, diverse epibiosis by sponges reported previously for Antarctic cidaroids.